Metabolic acidosis in hemodialysis patients: a review - Rezende,Luiza Raksa (2017)
Abstract Metabolic acidosis is highly prevalent in hemodialysis patients. The disorder is associated with increased mortality and its deleterious effects are already present in the predialysis phase of chronic kidney disease. Metabolic acidosis has been linked to progression of chronic kidney disease, changes in protein and glucose metabolism, bone and muscle disorders and cardiovascular disease. At present, the control of metabolic acidosis in hemodialysis is mainly focused on the supply of bicarbonate during dialysis session, but further studies are needed to set the optimum target serum bicarbonate and the best concentration of the bicarbonate dialysate. The present study reviews pathophysiological and epidemiological aspects of metabolic acidosis in hemodialysis patients and also addresses its adverse effects and treatment.